Separation force analysis and prediction based on cohesive element model for constrained-surface Stereolithography processes. (December 2015) - Liravi, Farzad; Das, Sonjoy; Zhou, Chi
Abstract: Constrained-surface based Additive Manufacturing (AM) processes have been widely used in both academia and industry for the past few years. Despite the advantages of constrained-surface based AM processes, it has not been widely used in practice. A main reason for this is that a substantial separation force is required to separate the cured part from the material vat during the pulling-up stage, which may damage the cured part and reduce the reliability of the process. The solutions proposed previously to reduce this separation force recommend using an intermediate coating material (e.g., Teflon and silicone films) between the cured part and the vat. This, however, has only negligible effects in reducing the separation force. In this work, the pulling-up process is modeled within the framework of mechanics-based principles. In particular, the cohesive zone model (CZM) is adopted to characterize the separation mechanism, and finite element (FE) simulation is carried out to investigate the separation process using the commercially available FE software, Abaqus. A new simple optimization scheme is also proposed to estimate the constitutive cohesive stiffness parameters from experimental measurements. These constitutive parameters are very difficult to estimate using the standard mechanical tests. The proposed work based on sound mechanics-based principles can be used for reliable prediction of pulling-up speed, and thus, is likely to be useful in devising an adaptive closed-loop system to control the pulling-up process and achieve a reliable AM approach. Highlights: We formulate cohesive zone model to characterize the separation process. We establish an optimization model to evaluate the mechanical parameters. The effectiveness of the proposed technique is validated by computer-simulated experiments. Fabrication performance can be significantly improved by the proposed approach.